Inactivation of Tissue Thromboplastin by Ultraviolet Irradiation - Åtland, S; Hvatum, M; Prydz, H (Thrombosis and Haemostasis, 1968)
Solutions of partially purified tissue thromboplastin have been irradiated with UV light of different wavelengths, and the resulting reduction in the procoagulant activity has been measured. The activity decreased as an exponential function of the dose. The action spectrum obtained was closely similar to the UV absorption spectrum of the thromboplastic preparations and had a maximum between 270-290 nm. The data suggested that the reduction in the procoagulant activity was caused by absorption of radiation energy in the protein part of the thromboplastic structure.